The use of mobile application to combat gadget addiction among university students in Malaysia / Nur Arifah Zahid - Zahid, Nur Arifah (2022)
Nomophobia means no mobile phone phobia. It is a mental condition that makes people afraid of getting disconnected from their phone. Carrying a tiny communicate technology device (gadget) in a pocket has become a normal event in recent years. Technology advances humanity by making ordinary tasks easier and more consistent. This research is to investigate the current condition of gadget addiction in Malaysia. In this context, gadget addiction among students increased. To analyze the factor of gadget addiction in Malaysia. The main focus of this research is to show beneficial it is to deploy a mobile application to reduce gadget addiction among Malaysian university students. The best solution for this method is to create a google form. This chapter will be discussing the qualitative and quantitative of the survey. The more sophisticated the world of technology, the higher the addiction to gadgets among students. Creating productivity and a time-tracker mobile application will help the student be productive and keep their focus. As the use of time-tracker mobile apps increases, more and more students become productive. The increase in student productivity decreases the issue of gadget addiction among students